2019
DOI: 10.1111/dar.13019
|View full text |Cite
|
Sign up to set email alerts
|

Contingency management treatment for methamphetamine use disorder in South Africa

Abstract: Introduction and Aims As South Africa, especially the Western Cape Province, faces an epidemic of methamphetamine use disorder, therapeutic approaches suited to the South African context are needed. This secondary analysis assessed retention and methamphetamine abstinence outcomes in response to an 8‐week pilot contingency management (CM) intervention trial of neural correlates of methamphetamine abstinence, exploring sociodemographic and clinical differences between responders and non‐responders. Design and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This study was part of a pilot project investigating the suitability of CM in treating MA Use Disorder in South Africa. It used a between-groups, cross-sectional design comparing outcomes to CM (complete response, partial response) among 29 individuals diagnosed with MA Use Disorder (DSM-5) to 20 healthy control participants, see Okafor et al (21). All participants completed neurocognitive and self-report measures, after which MA Use Disorder patients commenced an 8-week, escalating schedule, thrice-weekly, voucher-based CM intervention.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…This study was part of a pilot project investigating the suitability of CM in treating MA Use Disorder in South Africa. It used a between-groups, cross-sectional design comparing outcomes to CM (complete response, partial response) among 29 individuals diagnosed with MA Use Disorder (DSM-5) to 20 healthy control participants, see Okafor et al (21). All participants completed neurocognitive and self-report measures, after which MA Use Disorder patients commenced an 8-week, escalating schedule, thrice-weekly, voucher-based CM intervention.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…For example, CM participants are provided monetary vouchers in exchange for consecutive urine samples documenting abstinence from METH. A person with METH-positive or missing urine sample is moved down the escalating schedule [ 78 ]. The studies that assessed CM efficacy in reducing METH abuse or dependence showed positive outcomes when comparing MUD patients to control group participants or CM to other behavioral therapies [ 74 , 76 ].…”
Section: Current Treatments For Methamphetamine Use Disordermentioning
confidence: 99%
“…Additionally, the CM approach has been successfully used in maternal populations to reduce substance and tobacco use (Hand et al, 2017), including smoking cessation (Heil et al, 2008;Higgins et al, 2004Higgins et al, , 2012Tappin et al, 2015;Tuten et al, 2012), cocaine abstinence (Schottenfeld et al, 2011), polysubstance use (Jones et al, 2001;Svikis et al, 2007), and also alcohol use (Washio et al, 2017). The approach was also able to increase methamphetamine abstinence among adults in South Africa (Okafor et al, 2020). Providing incentives contingent on observed behavior facilitates behavior change by increasing the perceived value of a desirable behavior relative to the cost and effort of engaging in an undesirable behavior (Botvinick & Braver, 2015).…”
Section: Introductionmentioning
confidence: 99%